(3GdehGbas - (3YHO GdbGOQ Hf eMjj GdOjf Hf eUWaj GdMSfj GdLRGFQj,J (B1300 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3bGd JYGdi (B: ( (3hjVQH Gddg GdCeKGd ddfGS (B) (3hbGd JYGdi (B: ( (3Ef Gddg dG jSJMi Cf jVQH eKdkG eG HYhVI aeG ahbgG (B) s
(3BNQgG (B:s
(3hUdhG Ydi NjQ GdhQi NjQ eQSd hQhM gOGI GdNdb jhe ge OQ Ydjg UdGI Gddg eG bGd bGFd CeSYhO LGA GdSYO hGdNjQ hGdjSQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B45s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs